USE OF MODERN COMPUTER TECHNOLOGIES IN THE TREATMENT AND DIAGNOSIS OF DENTAL DISEASES - Ataxanov Sanjarbek Anvarovich; Ruzieva Rahnamo Behzod qizi (Bright Mind Publishing, 2025)
This article discusses how modern computer technologies help dentists treat teeth, take accurate dental images, detect hidden diseases, design crowns and prostheses, use lasers instead of drills, make diagnoses, as well as print teeth and models on 3D printers. The main methods are described: digital X-ray, 3D imaging, lasers, systems for manufacturing crowns and prostheses. An example of a practical assignment for students is given, as well as recommendations on using these technologies in education and practice. All of this makes treatment fast, accurate, and almost painless. The article explains how exactly computers assist dentists, provides an example of a practical assignment for students, and offers advice on using technologies in study and work.
Keywords: dentistry, computer, digital X-ray, 3D model, CAD/CAM, 3D printing, laser, telemedicine, diagnostics, treatment.